2015
DOI: 10.1016/j.otsr.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Is there any advantage in placing an additional calcar screw in locked nailing of proximal humeral fractures?

Abstract: The use of an additional unlocked calcar screw does not provide mechanical benefit in locked nailing of an unstable 2-part fracture of the surgical neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
6
1
1
Order By: Relevance
“…In 2012, Rothstock et al [18] presented increased stability and decreased varus displacement using a supplementary Bscrewin-screw^configuration and advocated an additional ascending calcar screw for SAN. Contrarily, Katthagen et al [19] showed that an additional unlocked calcar screw did not increase stability in a two-part fracture model fixed using a SAN construct.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Rothstock et al [18] presented increased stability and decreased varus displacement using a supplementary Bscrewin-screw^configuration and advocated an additional ascending calcar screw for SAN. Contrarily, Katthagen et al [19] showed that an additional unlocked calcar screw did not increase stability in a two-part fracture model fixed using a SAN construct.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in line with the results of Lill et al, the hybrid double plate osteosynthesis might give preferable results [ 30 ]. Especially for young patients with good bone substance and in cases of highly complex multi-fragment fractures, which were previously examined using hybrid double osteosynthesis, more rigid implants should be used [ 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cyclic compressive loading scenario with the humerus in a 20-degree abduction position was performed, similar to the investigations of Katthagen et al [ 18 ]. The force was applied in a sinusoidal form (1 Hz), ranging from a minimum of 10 N to a maximum of 250 N for 5000 cycles [ 14 , 17 , 18 , 22 ]. In the tests, the humerus were treated with normal saline every 10 minutes to hydrate them.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations